Menakar Respon Pengguna Instagram terhadap Program â€œMata Najwaâ€ Melalui Sisi dan Pandangan Politik - Saifuddin Zuhri; Irvia Amananda; Nanda Alya Karlina Amini; Tiara Febri Angellia (Ridwan Institute, 2021)
This study aims to find out how the program 'Mata Najwa' is responded by Instagram users as an educational program from the Political side which is a bridge to deliver information and connect people and government. This type of research used in this study is quantitative that uses the Use and Gratification approach and is carried out using the Instagram Polling feature. In this study, the total respondents are 258 Instagram users. The results of this study indicate that the program has responded well, is considered to educate the people well, and is expected to always be there and broadcast. Most of the respondents thought the 'Mata Najwa' program was used as a reference to attend the news that was being discussed hotly. Based on the results of the study showed that Mata Najwa has a positive image and educational value in the eyes of Instagram users.